XPS and structural studies of high quality graphene oxide and reduced graphene oxide prepared by different chemical oxidation methods - Al-Gaashani, R.; Najjar, A.; Zakaria, Y.; Mansour, S.; Atieh, M.A. (Ceramics international, 2019)
High quality graphene oxide (GO) and reduced graphene oxide (rGO) have been synthesized by chemical oxidation of graphite flakes via three modified Hummers methods using a mixture of sulfuric acid (H2SO4), phosphoric acid (H3PO4) and nitric acid (HNO3) as intercalating agents and potassium permanganate (KMnO4) and hydrogen peroxide (H2O2) as oxidizing agents. In this study the production of dangerously explosive gases was avoided. The temperature was carefully controlled using ice baths, ensuring the temperature was kept at the minimum during the reaction. The prepared samples were extensively characterized using various techniques including X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), high-resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). The results indicated greater presence of oxygen containing groups and an increase in the (C/O) ratio, both of which served as reliable indicators of high quality graphene oxide. Atomic ratio of carbon to oxygen (C/O) quantified by XPS was calculated to be 25.67, 1.81, 1.63, and 2.77 of graphite, GO-I, GO-II, and GO-III, respectively. As revealed by FTIR analysis, the GO-I had more hydrophilic oxygen functional groups compared to GO-II and GO-III.